Quantitative testing of the methodology for genome size estimation in plants using flow cytometry: a case study of the Primulina genus - Wang, Jing; Liu, Juan; Kang, Ming (Frontiers in Plant Science, 2015)
Flow cytometry (FCM) is a commonly used method for estimating genome size in many organisms. The use of flow cytometry in plants is influenced by endogenous fluorescence inhibitors and may cause an inaccurate estimation of genome size; thus, falsifying the relationship between genome size and phenotypic traits/ecological performance. Quantitative optimization of FCM methodology minimizes such errors, yet there are few studies detailing this methodology. We selected the genus Primulina, one of the most representative and diverse genera of the Old World Gesneriaceae, to evaluate the methodology effect on determining genome size. Our results showed that buffer choice significantly affected genome size estimation in six out of the eight species examined and altered the 2C-value (DNA content) by as much as 21.4%. The staining duration and propidium iodide (PI) concentration slightly affected the 2C-value. Our experiments showed better histogram quality when the samples were stained for 40 minutes at a PI concentration of 100 µg ml-1. The quality of the estimates was not improved by one-day incubation in the dark at 4 °C or by centrifugation. Thus, our study determined an optimum protocol for genome size measurement in Primulina: LB01 buffer supplemented with 100 µg ml-1 PI and stained for 40 minutes. This protocol also demonstrated a high universality in other Gesneriaceae genera. We report the genome size of nine Gesneriaceae species for the first time. The results showed substantial genome size variation both within and among the species, with the 2C-value ranging between 1.62 and 2.71 pg. Our study highlights the necessity of optimizing the FCM methodology prior to obtaining reliable genome size estimates in a given taxon.